Designing low-cost "heart healthy bread": optimization using linear programing and 15-country comparison. Issue 1 (December 2016) - Wilson, Nick; Nghiem, Nhung; Ryan, Sian; Cleghorn, Christine; Nair, Nisha; Blakely, Tony
Abstract Background Bread is an important component of the diet in many countries and provides needed nutrients but also typically too much of other nutrients e.g., sodium. We therefore aimed to use linear programing to determine the optimal design of low-cost "heart healthy bread" (HHB) and to compare the results with commercial breads in 15 countries. Methods Optimization using linear programing focused on achieving set loaf prices (at NZ$1.5 and $3) and for a range of minimal sodium levels. Then within those constraints, levels of alpha-linolenic acid (ALA) were maximized, then dietary fiber, and then polyunsaturated fatty acids. Data from New Zealand (NZ) was used for the HHB designs and comparison nutrient and price data came from breads in 15 high-income countries. Results The optimized loaf costing NZ$1.50 in ingredients (HHB$1.5) was superior to the commercial white loafs in three out of the eight heart health nutrient categories. The optimized loaf that was high in linseed and cost NZ$3 in ingredients (HHB$3), was nutritionally superior to the commercial loafs with seeds/nuts in six out of the eight heart health categories (i.e., in terms of sodium, potassium, fatty acid ratio and fiber). In terms of value-per-weight, a commercial white loaf from the UK was slightly cheaper than the HHB$1.50 loaf (at US$0.07 vs US$0.10 per 100 g loaf). But compared to the other seed/nut loafs, the HHB$3 loaf was the best value at US$0.17 per 100 g, vs a mean of US$0.85 per 100 g across international comparators. Conclusions This proof-of-concept study suggests it is possible to design breads that are nutritionally superior to commercially available breads from a heart health perspective, as well as being lower cost. Such HHB designs could be promoted by health agencies and utilized in conjunction with a government-funded bread voucher system for those at high risk of cardiovascular disease.